EFFECT OF KETAPANG (Terminalia Catappa L) LEAVES SOLUTION ON THE HURTING POWER OF LELE SANGKURIANG (Clarias sp) EGGS - Ulfah Rana Zarqa; Oktamalia Oktamalia; Suharun Martudi; Novita Hamron; Hety Novitasari (Fakultas Pertanian, 2023)
Sangkuriang catfish is a variant of today's superior catfish that is widely developed and currently very popular in the community. Because of its good taste and high nutritional content, catfish has a high selling value. To increase the production of freshwater fisheries, what needs to be considered is the quality of eggs and seeds as well as the parent; cultivation activities often found problems with catfish eggs are adhesive or clumping eggs that result in eggs lacking oxygen, thus inhibiting embryonic development. In addition, eggs are often attacked by mold resulting in rotting eggs. Ketapang leaf extract can prevent and treat fish that are attacked by diseases caused by bacteria. Ketapang leaves contain tannin and flavonoid compounds that function as anti-bacterial. The study aims to determine the effect of egg soaking on the dose of ketapang leaf solution on the hatchability of Sangkuriang catfish eggs. This research was conducted from August to September 2021 in Gunung Alam Arga Makmur Village, North Bengkulu Regency. The study used a completely randomized design with 4 treatments, namely A0 = 0 ml (control), A1 = 1 ml ketapang leaf solution, A2 = 3.75 ml ketapang leaf solution, and A3 = 5 ml ketapang leaf solution. The treatment was repeated 3 times. The results showed that the administration of ketapang leaf extract at a dose of 5 ml had a natural effect (P <0.05) on the hatchability of Sangkuriang catfish eggs by 44.67%. The treatment with the lowest egg hatchability was achieved by 0 ml at 22.00%.